The Role of Cross-Sectoral Cooperation, Family Support, and Knowledge on the Activeness of Prolanis Participants - Rodiah Pulungan; Nurhayati Nurhayati; Tria Astika Endah Permatasari; Syamsul Anwar (GLOBAL HEALTH SCIENCE GROUP, 2024)
Prolanis is a proactive health service system and an integrated approach involving the community in health maintenance to achieve optimal quality of life with effective and efficient healthcare costs. Objective: The aim of this research is to analyze the cross-sectoral role, family support, and knowledge concerning the activity level of participants in the Prolanis program at the Cempaka Putih District Community Health Center. Method: This study was conducted at the Cempaka Putih District Community Health Center from November 2022 to July 2023 with 65 respondents based on total sampling. Data collection was done using questionnaires and interviews with three types of instruments, covering demographic data, Prolanis information and family support, and cross-sectoral roles. Data analysis employed Multiple Logistic Regression. The research revealed six variables with p-values < 0.05 in non-parametric tests: age, education, occupation, cross-sectoral roles, family support, and knowledge. Results: Logistic regression analysis resulted in p-values < 0.25 with odds ratios: age OR: 2.113; education OR: 2.695; occupation OR: 3.091; cross-sectoral roles OR: 1.431; knowledge OR: 2.179. Conclusions: There is a relationship between age, education, occupation, cross-sectoral roles, and knowledge factors with the activity level of Prolanis participants at the Cempaka Putih District Community Health Center.